Advanced courses of mathematical analysis III : proceedings of the third international school, La Rabida, Spain, 3-7 September 2007 - Delgado Sańchez, Juan M.; Domínguez Benavides, T. (Tomás), 1951- (World Scientific, 2008)
This volume comprises a collection of articles by leading researchers in mathematical analysis. It provides the reader with an extensive overview of the present-day research in different areas of mathematical analysis (complex variable, harmonic analysis, real analysis and functional analysis) that holds great promise for current and future developments. These review articles are highly useful for those who want to learn about these topics, as many results scattered in the literature are reflected through the many separate papers featured herein.